1989
DOI: 10.1016/s0022-5347(17)41345-0
|View full text |Cite
|
Sign up to set email alerts
|

The pH Analysis of Papaverine-Phentolamine and Prostaglandin E 1 for Pharmacologic Erection

Abstract: Although papaverine-phentolamine preparations are being employed for pharmacologic erection programs across the nation, their chemical properties have not been described in the literature. We found that the pH of papaverine-phentolamine solution in all concentrations tested remained less than 4.0. Attempts to buffer the solution resulted in a precipitate at a pH greater than or equal to 5.0. The pH of prostaglandin E1 was less than 5.0 but could be easily buffered to pH 7.4 or even 10.75 and remained stable. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…Although, it is said that papaverine may have signi®cant in¯uence on cavernous blood gas analyses, 14 our results of cavernous pO 2 is similar to results of electroerection, visual-tactile sexual stimulation and intracavernosal injection of the PGE 1 3,10,13 which have no adverse effects on cavernous pH.…”
Section: Discussionsupporting
confidence: 64%
“…Although, it is said that papaverine may have signi®cant in¯uence on cavernous blood gas analyses, 14 our results of cavernous pO 2 is similar to results of electroerection, visual-tactile sexual stimulation and intracavernosal injection of the PGE 1 3,10,13 which have no adverse effects on cavernous pH.…”
Section: Discussionsupporting
confidence: 64%
“…However, there have been a few reports of syncope and other systemic events.l 41 ,95] The nature and incidence of adverse events reported in elderly users of intracavernous alprostadil are similar to those found in the general populationJ47, 48] The frequency of adverse events associated with intracavernous alprostadil use is affected by a number of factors, possibly including the pH of the formulation, [33,45,50,67,[96][97][98] the dose, [44,51] the amount of training patients receive [67,99] and the type of injection device. However, there have been a few reports of syncope and other systemic events.l 41 ,95] The nature and incidence of adverse events reported in elderly users of intracavernous alprostadil are similar to those found in the general populationJ47, 48] The frequency of adverse events associated with intracavernous alprostadil use is affected by a number of factors, possibly including the pH of the formulation, [33,45,50,67,[96][97][98] the dose, [44,51] the amount of training patients receive [67,99] and the type of injection device.…”
Section: _ Tolerabilitymentioning
confidence: 97%
“…The pH of papav erine is less than 4.0. Buffering by the blood will lead to the precipitation of papaverine and may cause primary intracorporéal scarring when injected into the corpus cavemosum [10]. Repeated injections might cause fibro sis of the penile shaft.…”
Section: Discussionmentioning
confidence: 99%
“…Other actions include the subsi dence of inflammation, the inhibition of platelet aggre gation, the protection against tissue damage and the sta bilization of proteases [1]. The pH of PGEi was less than 5.0 but could be easily buffered to pH 7.4 or even 10.7 and then remained stable [10]. Some authors reported that it may be metabolized locally and that 70% of cir culating PGEi is cleared through the lungs [13], The rapid decline of circulating PGEj might minimize the systemic side effects and the incidence of priapism.…”
Section: Discussionmentioning
confidence: 99%